International Monetary Fund Annual Report 1976. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1976)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1976. The report highlights that in mid-1976, the world economy was completing the first year of recovery from its most severe recession in four decades. Production in the industrial countries was again expanding at a satisfactory pace, and rates of inflation were considerably below those experienced in 1974 and the first half of 1975. By the past standards, however, both unemployment and inflation remained exceptionally high for the early phase of a cyclical upswing.